Sighting patterns and habitat use of marine mammals at Guafo Island, Northern Chilean Patagonia during eleven austral summers - Seguel, Mauricio; Pavés, Héctor J. (Revista de Biología Marina y Oceanografía, 2018)
The chiloense marine ecoregion, at the Northern Chilean Patagonia, has been considered a hotspot of marine mammal diversity, yet little is known regarding specific sites used by these species for reproduction, nursing, refuge, and foraging. This information is critical for proper spatial ecosystem planning and conservation of marine resources. In the austral summers of 2004 through 2008, and from 2012 to 2017, the presence, distribution, and behavior of 13 species of marine mammals was recorded at Guafo Island, an oceanic island located in the center of the chiloense ecoregion. Guafo Island is an important reproductive and feeding site for South American fur seals (Arctocephalus australis australis), South American sea lions (Otaria byronia) and marine otters (Lontra felina), and an important feeding, nursing, and transit location for humpback whales (Megaptera novaeangliae), Orcas (Orcinus orca), and blue whales (Balaenoptera musculus). We also recorded occasional sightings of fin whales (B. physalus), southern right whales (Eubalaena australis) and Peale’s dolphins (Lagenorhynchus australis). The island coastline also serves as refuge for molting Southern elephant seals (Mirounga leonina) and vagrant Subantarctic fur seals (Arctocephalus tropicalis). The information presented here highlights Guafo Island as an important breeding, shelter, and feeding site for marine mammals in Chile. The growing anthropogenic pressure on this ecosystem emphasizes the importance of formal protection of this island as a priority site for marine conservation in the Northern Patagonia of Chile.